Penggunaan Bahasa Indonesia Pada Surat Dinas Serta Implikasinya Terhadap Pembelajaran Menulis Di Sekolah - Huda, Muhammad Binur; Septiana, Ari (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
Writing official letters should use good and correct language. This is to make it easier for readers to understand the writing that will be written. The data obtained came from official letters at the Maospati District Office. After the data was analyzed, many errors were found, including the use of spelling, word choice and effective sentences. Errors in the use of spelling contained in official letters at the Maospati District Office, namely errors in writing capital letters, italics, bold letters, prepositions, abbreviations and acronyms, numbers and numbers, periods, commas, colons, hyphens, and a slash. The most errors lie in writing capital letters, while the fewest errors lie in writing numbers and numbers. Errors in the use of word choices contained in official letters at the Maospati District Office, namely errors in the use of words that are non-standard, unfamiliar, impolite and inaccurate. The most errors lie in writing inaccurate words, while the fewest errors lie in writing impolite words. Errors in the use of effective sentences contained in official letters at the Maospati District Office, namely errors in the use of sentences that are not commensurate, not parallel, not economical, not accurate and illogical.